Private and State Differences of Elementary Schools in Implementing Mathematics Learning At Covid-19 Era - Dila Anggaraini Dila (Mathematics Research and Education Journal, 2022)
This study aims to qualitatively and quantitatively describe the effectiveness of learning mathematics in the covid era in private and public elementary schools. The population of this research is elementary school students in Pekanbaru. The research sample was two Pekanbaru elementary schools which were selected purposively according to the problems studied based on the school's style or strategy in improving learning outcomes. The research instrument is in the form of documentation of student learning outcomes and in-depth interviews with the principals of each school. Analysis of research data using independent t-test and descriptive qualitative data analysis. The results showed that there was a significant difference between elementary school mathematics learning in private and public schools in implementing mathematics learning. These results can be seen from the results of the descriptive test and the independent t-test with a significance of 0.00 where the private mathematics learning outcomes are better than the public ones. From the results of interviews obtained information that private schools provide additional lessons to students by coming to students' homes.